Analysis of the Impact of Digitalisation of Devices, Digitalisation of Platforms and Digitalisation of Media on Perceptions of Online Shopping among Millennials and Gen-Z in Medan City - Sanjaya, Arif; Yurika, Yurika; Sibarani, Hendra Jonathan; Sipayung, Sari Mariahma Nova (International Journal Of Economics Social And Technology (IJEST), 2024)
Digitalisation is currently one of the development and operation of a device, platform and media increasingly used by Millennials and Gen-Z to provide information or sell products. Product digitalisation is not only in marketing but also as a promotional medium to create consumption patterns of application users who are highly dependent on lifestyle changes and perceptions of online shopping applications. In this study using quantitative methods are research based on the philosophy of positivism, used to research on specific populations and samples. This study used 100 samples from Medan Helvetia district using cluster sampling method. The results of this study show that the digital devices have a positive and significant influence on the perception of online shopping, the platform digitalisation does not have a positive and significant influence on the perception of online shopping, the media digitalisation has a positive and insignificant influence on the perception of online shopping among millennials and gen-z in Medan City. Digitalisation in online shopping applications has a huge impact on the perception of online shopping application users because the information obtained becomes faster and there is an increase in customer consumptive patterns